Post-war memorialisation as everyday peace? Exploring everyday (dis-) engagements with the Maoist martyrs' gate of Beni Bazaar in Nepal. Issue 5 (3rd September 2019) - Lundqvist, Martin
ABSTRACT: The academic debates on post-war memorialisation and everyday peace tend to appear in relative isolation from one another. Yet, there is arguably much to gain from integrating them, by exploring how – and to what effect – post-war monuments are incorporated into everyday life. To this end, this article studies the everyday interactions that residents of Beni Bazaar, Nepal, have developed in relation to the recently erected Maoist martyrs' gate. As such, narrative ellipsis, local co-operation and popular culture are identified as three distinct ways in which the gate has become entangled with everyday life in the city. I argue that these everyday interactions represent inherently political acts, which in subtle ways serve to destabilise the politically divisive 'message' of the post-war monument. Hence, it makes sense to think of these everyday interactions as a form of bottom-up peace-building in their own right – albeit to varying degrees.